The Values of Da'wah in Meurukon Oral Speech to the Acehnese Community in Aceh Besar Regency - Fakhri; Siti Maisarah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
The existence of meurukon traditional art has practically become endangered due to the lack of skill and knowledge transfer from older to younger generations. This phenomenon caused the lack of awareness of many Acehnese societies on the Islamic values (dawah) contained in the meurukon tradition. This study employed a qualitative approach. The result of this study shows that there is a relation and reciprocal relationship between the culture of meurukon and dawah values based on the Islamic teachings. The dawah values within the meurukon traditional art are as follows; 1. The value of Tauheed, 2. The value of Amar bil Maroof wa Nahi anil Munkar, 3. The value of truth, 4. The value of worship, 5. The value of silaturrahim, 6. The value of Akhlaq, 7. The value of Tabligh, 8. The value of art integration. Hence, it can be concluded that meurukon is an art of dawah in the form of mujadalah. Meurukon plays an important role in transferring knowledge and dawah values to society by using 2 approaches. Firstly, by using the media such as; meunasah, mosque, and pesantren. Secondly, the integration of art and culture, which tends to use the aesthetic value in the society through stanzas and poems delivered in the form of dialogue (mujadalah). As a solution, some regencies in Aceh province have actively re-promoted meurukon by regularly organizing the competition of meurukon in the sub-districts and regency area.